Capital Movements and International Payments in Postwar Europe - Hoffman, Michael L. (The Review of Economics and Statistics, 1949)
EFFORTS to construct a workable system of international payments for Europe since the end of World War n1 have concentrated almost exclusively on the problem of finding suitable machinery to handle current account transactions between monetary areas. Capital transactions have been ignored, deprecated, and made as difficult as possible. This is in accord with the attitude toward international capital movements that has been dominant for the past ten or fifteen years. The concern of national treasuries to prevent a recurrence of the hot money movements of the I930's led the drafters of the Bretton Woods agreements to place capital movements in a kind of limbo where exchange controls, supposedly committed to let current transactions go free after the transition period, could exercise their ingenuity and regulate to the controllers' hearts' content. The resources of the International Monetary Fund cannot be used to finance capital movements unless the Fund's holdings of a currency remain below seventy-five per cent of that member's quota for more than six months, and then only if the effect of the operation does not raise holdings of that member's currency above seventy-five per cent and does not lower the Fund's holdings of the desired currency below seventy-five per cent of the appropriate quota. The existence of commitments to service debts in a money other than that of the debtor is regarded as an almost intolerable nuisance by technicians who have the duty of preparing and overseeing bilateral payments accords. Broadly speaking, a capital export, if it comes before the authorities at all, is treated by them as a hard currency transaction, whether it involves a movement of funds to a harder currency area or to an area whose money is as soft as that of the capital exporting country. Europe has innumerable committees dedicated to the removal of restrictions on international trade, and a good many sober groups working to establish greater freedom of movement across frontiers for labor. There are no committees to improve international capital movements, although there are lots of committees producing all kinds of reasons why countries need to import capital. The Bank for International Settlements is almost a lone voice in urging economic policy makers to remember that free movement of capital, both short and long term, has in the past been an important aid in the economic development of the world as a whole. 1 The problem of establishing greater convertibility of European currencies is commonly analyzed on the basis of the unstated assumption that there are no capital movements between monetary areas or between European and non-European parts of a given monetary area-i.e., that convertibility is possible only under circumstances in which net deficits and net surpluses on current account could be completely cleared, exception being made for more or less net capital inflow from the United States to European monetary areas as a group. The neglect of capital movements in current discussion and policy making has already led to serious practical difficulties. The United Kingdom balance of payments estimates have been consistently thrown off, and rather badly off, by the appearance of unexpected capital movements, both within the sterling area and with other areas. The figures are not very good, although Britain is the only country in Europe for which respectable data exist. At the time of the negotiations for the first U.S. loan to Britain, care was taken to establish criteria for disposing of the three billion odd pounds sterling of debt held by the (mostly sterling area) recipients of Britain's heavy overseas Dayments during the war. There is